Nephtys bangladeshi n. sp., a new species of Nephtyidae (Annelida: Phyllodocida) from Bangladesh coastal waters - Hossain, M. Belal; Hutchings, Pat (Zootaxa, 2016)
A new species of nephtyid polychaete, Nephtys bangladeshi n. sp., from the intertidal zone of Bangladesh is described. It is characterized by having a pharynx with 9 pairs of bifid terminal and 14 rows of subterminal papillae, each subterminal row with 5–7 papillae, as well as the presence of branchiae from chaetiger 7 to 27. The new species is compared with other species from the Indo-Pacific. This is the first report of a new polychaete species from Bangladesh coastal waters.